Subsarcolemmal and interfibrillar mitochondria display distinct superoxide production profiles. (March 2015) - Crochemore, C.; Mekki, M.; Corbière, C.; Karoui, A.; Noël, R.; Vendeville, C.; Vaugeois, J.-M.; Monteil, C.
Abstract: Cardiac subsarcolemmal mitochondria (SSM) and interfibrillar mitochondria (IFM) subpopulations display distinct biochemical, morphological, and functional characteristics. Moreover, they appear to be differently influenced during cardiac pathologies or toxic injuries. Although mitochondrial reactive oxygen species seem to play a critical role in cardiac function and diseases, limited information exists about the superoxide production characteristics of these mitochondrial subpopulations. In this work, using direct measurement of superoxide by electron paramagnetic resonance, we showed that differences in superoxide production profiles were present between cardiac IFM and SSM, in terms of intensity and major sites of superoxide generation. In SSM incubated with glutamate plus malate as substrates, the total observed superoxide levels were significantly higher than those observed with IFM, with an important contribution of the NADH-oxidizing site of complex I (site If) and the quinol-oxidizing site of complex III (site IIIQ0). In both IFM and SSM, succinate leads to similar rates of total superoxide levels with a substantial role for contribution of reverse electron transfer. Finally, using two spin probes with different membrane permeabilities, our data on complex III showed direct intra- and extra-mitochondrial superoxide release whereas complex I- and II-dependent superoxide were exclusively released inside the mitochondria, confirming previous studies. Feasibility of this approach to measure intra- and extra-mitochondrial superoxide levels and to characterize distinct superoxide production profiles of cardiac IFM and SSM has been demonstrated.